The challenges in raising autistic children: The voices of mothers - Hazlina Abdullah; Ratnawati Mohd Asraf; Myra Aidrin Mohd Ali; Nursyuhada' Ab Wahab; Dini Farhana Baharudin (International Journal of Evaluation and Research in Education (IJERE), 2022)
Autism spectrum disorder (ASD) is defined as a lifetime developmental disorder usually identified by social interaction impairment, communication deficits, and repetitive behavior. The cases of children detected with ASD are rising globally, including Malaysia. Parents, as the prime caregiver to these children, face numerous challenges due to what is entailed in taking care of their children. This paper describes a case study where we examined the views and experience of three mothers, each of whom has an ASD child. Data were gathered through face-to-face semi-structured interviews, after which they were transcribed and analyzed using the thematic analysis method. The mothers narrated that the challenges they encountered include the difficulty they had in initially accepting their child’s diagnosis; labelling and discrimination; phase-based temporal challenges; endless physical, emotional, and mental sacrifices; finding the strength and patience to deal with the situation; academic vs. non-academic struggles, as well as their own coping mechanisms. This paper concludes with the need to provide support for parents-especially mothers-to enable them to overcome their challenges and focus on the development of their autistic children.